Taurine inhibits acute ammonia-induced oxidative stress, immune response, and apoptosis of large yellow croaker (Larimichthys crocea) during keep-live transport - Xin Zhao; Zhenkun Xu; Jun Mei; Jing Xie (Journal of Agriculture and Food Research)
Ammonia is thought to be the main chemical contaminant that stresses fish during keep-live transport. Taurine has antioxidant properties. This research investigated the oxidative stress, immune response, and apoptosis of large yellow croaker (Larimichthys crocea) during keep-live transport, and the alleviation effect of taurine. The findings demonstrated that ammonia stress might cause the transcription of the stress-related parameter (Hsp70) gene and antioxidant enzymes (SOD, CAT, and GPx) to be upregulated. Taurine administration could lessen the negative impact of ammonia stress. The results showed that ammonia stress might also lead to the up-regulation of stress-related parameter (Hsp70) gene and antioxidant enzymes (SOD, CAT and GPx). Taurine could alleviate the negative effects of ammonia stress. Taurine might reduce the production of reactive oxygen species (ROS), and the content of malondialdehyde (nmol/mL) could be decreased from 96.09 (AM group) to 62.15 (50TAU + AM group), thus reducing DNA damage. SOD and GPx activities increased from 3.47 to 13.23 (AM group) to 9.4 and 55.48 (50TAU + AM group), immunosuppression (lysozyme activity increased). In conclusion, taurine may alleviate the adverse effects of ammonia stress on fish physiology. This research will help elucidate the mechanism of taurine in alleviating ammonia stress. This discovery offers a potential new approach for reducing ammonia stress of large yellow croaker in the future.